Téléconseillers et community managers : quelles professionnalités pour la médiation entreprise-publics à l’heure du numérique? - Fabien Bonnet (Communiquer)
The community manager is emerging as a key figure in professional discourse in communication and marketing. This article offers a parallel with the research that has been dedicated, in the 2000s, to another figure at this time in full visibility: the call center agent at work in the context of customer relationship management strategies. Using semi-structured interviews conducted with communication professionals and students, this research aims to highlight the shift of the professional field of customers/company mediation, from an individual and already complex perspective, adapted to the telephone exchange, to a vision adding the opportunities offered by digital networks in terms of hybrid formats and practices.